Mother's pre‐pregnancy BMI is an important determinant of adverse cardiometabolic risk in childhood. Issue 6 (20th March 2015) - Tan, Hong Chang; Roberts, James; Catov, Janet; Krishnamurthy, Ramkumar; Shypailo, Roman; Bacha, Fida
<x xml:space="preserve">Abstract</x> Objective Maternal adiposity is associated with poor offspring cardiometabolic health. We aimed to evaluate the relationship of maternal pre‐pregnancy body mass index (BMI) on the BMI, body composition and cardiometabolic characteristics of the offspring. Methods Forty offspring of overweight/obese mothers (O‐OW) and 28 offspring of normal weight mothers (O‐NW) underwent evaluation of body composition, abdominal fat distribution, blood pressure measurement, fasting lipids and an oral glucose tolerance test. The anthropometric and cardiometabolic characteristics of O‐OW were compared with those of O‐NW, and the relationship to maternal BMI was evaluated. Results Subjects (mean age: 12.6 ± 0.4, female: 52.9%) had similar gestational age, birth weight, age, gender, and Tanner stage. However, O‐OW had a significantly higher BMI (24.4 ± 1.2 vs. 19.7 ± 0.8 kg/m2, p = 0.001), % body fat (31.7 ± 1.6 vs. 24.6 ± 1.1%, p < 0.001), visceral fat (41.9 ± 4.7 vs. 26.1 ± 3.9 cm2, p = 0.012) with no difference in lean body mass compared with O‐NW. O‐OW had lower whole body insulin sensitivity index (WBISI) with an adverse cardiovascular disease risk profile [higher blood pressure (BP), triglycerides to high‐density lipoprotein (HDL) ratio, hs‐C‐reactive protein (CRP) and lower HDL]. In addition to offspring's %body fat (β = −0.60, p < 0.001), maternal pre‐pregnancy BMI (β = −0.19, p = 0.046) contributed significantly and independently to the offspring's WBISI (R2=0.55, p < 0.001). Conclusions High pre‐pregnancy BMI is an important contributor to excess adiposity, insulin resistance, and cardiometabolic disease risk in the offspring during childhood.